PENTINGNYA PENDIDIKAN INTERAKSI SOSIAL UNTUK KESEJAHTERAAN SOSIAL LANJUT USIA - Murlis, Murlis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Entering old age, people will experience setbacks, especially physically and psychologically. However, this does not mean that changes in physical and psychological conditions make the elderly feel useless, or people who think that the elderly are useless, as argued by Argyo (2007), in many cultures and societies the elderly have a role and position. as a person who is respected, is considered to have more knowledge and experience so that it becomes a place for questions and advice for young people. Changes in systems and structures in society have implications for the role and position of the elderly in the family and society. For example, the change from a broad family form in a traditional society to a nuclear family implies that the elderly will experience life alone. Living conditions themselves are far from the attention of the family and will bring problems to the elderly, especially the elderly who do not have enough economy to meet their daily needs. Elderly people will live in poverty if there is no interaction with other people, causing various diseases in their lives.